A Preliminary Study of Internet Based Ticketing System Impacts on Selected Travel Agencies in Malaysia - Khuja, Mohamed Saleh; Bohari, Abdul Manaf (Journal of Asian Business Strategy, 2012)
The impact of the Internet based ticketing systems has made information easily accessible to consumers and has therefore established a direct link between consumers and suppliers. This study focuses on the impact of the Internet based ticketing systems on the travel agency in Langkawi, Malaysia. The major method was included in-depth interviews with travel agents to explore and refine the major issues that faced by the industry. Interviews with consumers were also carried out to ascertain the role of travel agents in the Internet based ticketing systems. The major finding shows that disintermediation is particularly pronounced in the relationship between airlines and travel agents. Therefore, the main pressure factors on the travel agency market in Malaysia since the emergence of the Internet are identified as airline commission cuts, suppliers selling directly to consumers and the rise of online consumers who seek self-service travel arrangements. In conclusion, travel agents perceives ICT as a strategic tool and are oriented towards consumers appears to have a business edge.